"The Only State Completely in the Arctic" The Evolution of Iceland's Arctic Identity - Jenný Lárentsínusdóttir 1993- (2022)
The evolution of Iceland‘s Arctic Identity since 2011 has been motivated by various events including the debated cooperation between the Arctic five since 2008, the importance Iceland has given historically to being recognised as equal to other sovereign states and the recent importance that has been given to the Arctic globally. Apart from Olafur Ragnar Grimsson the former president, Iceland did not give the same level of importance to the Arctic prior to the grouping of the Arctic five as it did after that event, and shortly after, or in 2011, put the Arctic as a top priority of its foreign affairs agenda. What followed was the construction of Iceland‘s Arctic Identity, where politicians have actively advocated for Iceland‘s Arctic-ness. The politicians make an effort of asserting Iceland as a Coastal state and claim Iceland is the only state completely in the Arctic. This thesis is a case study that will explore the evolution of Iceland‘s Arctic Identity, analysing specifically how it has been portrayed by politicians. It will do so by applying the method of discourse analysis. The main theme that emerged from the analysis of Iceland‘s Arctic identity discourse as portrayed by politicians were: The use of Iceland‘s geographical position and Iceland being the only sovereign state fully within the Arctic according to their interpretations, environmental characteristics in Iceland that have commonly been associated with the Arctic, as well as the narrative of Icelandic people being Arctic and how the Arctic has affected Iceland‘s society and livelihood. Þróun á því, sem kalla mætti norðurslóðaímynd eða sjálfsmynd Íslands sem norðurslóðaríki, hefur síðasta rúman áratug eða svo markast af nokkrum meginþáttum. Þar verður helst litið til samstarfs þjóðanna sem mynda hópinn „Artic five“ (Standríkin fimm) síðan 2008 og umræður á þeim vettvangi, jafnframt til þeirrar áherslu sem Ísland hefur með vísan til sögulegra röksemda lagt á mikilvægi þess að verða metið í því samstarfi til jafns við önnur fullvalda ríki, auk ...